Konsep Slow Bar Coffee dan Keputusan Pembelian Kedai Kopi Ngopi Dipit Serang - Hafidz Hanafiah; Devi Rosalina; Aria Cendana Kusuma; Irma Nurmala Dewi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The Slow Bar Coffee concept was introduced in 2002 in Oslo Norway by Tim Wendelboe. This concept not only serves coffee menus to customers, but there is a discussion space created there. The aim of this research is to determine the concept of slow bar coffee offered by the Ngopi coffee shop in Dipit Serang and customer purchasing decisions which are influenced by social media marketing, product quality and location. The method used uses observation methods for the slow bar coffee concept and quantitative methods for purchasing decisions. The number of samples taken was 80 respondents. The results of the research found that the concept of slow bar coffee drinking coffee in the pit is a concept that has been carried out by baristas with customers in introducing and discussing the world of coffee. Purchasing decisions are also influenced by social media marketing, product quality, and location. So it can be concluded that social media marketing, product quality and location can influence purchasing decisions and the concept of slow bar coffee served by coffee shops in Serang City.